Etika Calvinisme sebagai Fondasi Toleransi dalam Kehidupan Beragama - Hamdani, Dani; Kusmayani, Anisa Eka Putri (Integritas Terbuka: Peace and Interfaith Studies, 2024)
This research aims to explore Calvinist ethics as a foundation for tolerance in religious life within pluralistic societies. Calvinist ethics, with its principles of predestination, hard work, simplicity, and social responsibility, demonstrates significant potential to foster social harmony and interfaith tolerance. This study employs a qualitative approach through a literature review of relevant primary and secondary sources. The findings indicate that the doctrine of predestination provides a theological foundation for respecting individual freedom and fostering mutual respect. Furthermore, the principles of hard work and simplicity in Calvinism promote the reduction of social disparities, which are among the primary causes of religious conflict. In the Indonesian context, these values can be applied to overcome social segregation and create inclusive interfaith relationships. Examples from Calvinist communities in Indonesia and the Netherlands confirm how Calvinist principles facilitate interfaith dialogue and support social harmony. This research expands previous discussions by introducing a new dimension to understanding the relationship between Calvinism and religious pluralism. The integration of love, justice, and religious freedom into the modern societal context establishes Calvinism as not only a theological tradition but also an ethical framework relevant for addressing the challenges of religious pluralism.